Original paperAdjuvant vaginal cuff brachytherapy for high-risk, early stage endometrial cancer - Eldredge-Hindy, Harriet Belding; Eastwick, Gary; Anne, Pramila Rani; Rosenblum, Norman G.; Schilder, Russell J.; Chalian, Raffi; Zibelli, Allison M.; Kim, Christine H.; Den, Robert (Journal of Contemporary Brachytherapy, 2014)
Purpose: To report outcomes following adjuvant high-dose-rate vaginal brachytherapy (VBT) with or without chemotherapy for high-intermediate risk (HIR) and high-risk, early stage endometrial cancer as defined in Gynecologic Oncology Group trial 0249. Material and methods: From May 2000 to January 2014, 68 women with HIR and high-risk endometrial cancer underwent surgical staging followed by VBT. Median VBT dose was 21 Gy delivered in three fractions prescribed to 0.5 cm depth. Paclitaxel 175 mg/m 2 and carboplatin area under the curve 6 was administered every 21 days in sequence with VBT. Actuarial survival estimates were calculated using the Kaplan-Meier method. Results: Patient demographics included a median age of 66 years (range: 36-91) and stages IA (49%), IB (38%), and II (13%), respectively. Thirty-one (46%) patients had HIR disease with endometrioid histology, and 33 (48%) patients had serous or clear cell histology. Thirty-seven (54%) patients received a median 3 cycles (range: 3-6) of chemotherapy in addition to VBT, and 65 patients (96%) completed all prescribed therapy. During a median follow up of 33.1 months (range: 4.0-161.7), four patients have recurred, including one vaginal recurrence. The 3-year estimates of vaginal, pelvic, and distant recurrences were 1.9%, 2.4%, and 9.1%, respectively. The 3-year rates of disease-free and overall survival were 87.7% and 93.9%, respectively. Conclusions : Early outcomes with adjuvant VBT with or without chemotherapy demonstrate high rates of vaginal and pelvic control for women with HIR disease. Early vaginal and pelvic relapses in high-risk patients suggest that pelvic external beam radiotherapy is warranted in this subgroup, but additional data from large phase III trials is warranted.